Recurrent Sigmoid Volvulus in Children-Our Experience and Systematic Review of the Current Literature - Jonathan Hencke; Steffan Loff (MDPI AG, 2023)
Sigmoid volvulus (SV) occurs rarely in children. After encountering two cases of recurrent SV, we reviewed the literature to define the recurrence risk, identify outcome predictors and to give treatment recommendations. We found 256 cases reported in children (mean age 10.2 years, gender ratio (m:f) 2.3:1). Associations exist with Hirschsprung disease (HD) in 10%, neurodevelopmental disorders in 10.9% and chronic constipation in 10.2%. Common symptoms and clinical signs were abdominal pain (85%), distension (85%), tenderness (54%) and vomiting (59%). Signs of peritonitis were present in 14% and indicated a gangrenous sigmoid (X2 = 45.33; p < 0.001). A total of 183 had abdominal radiographs, and 65% showed a positive 'coffee-bean-sign'. Contrast enemas were positive in 90%. A total of 124 patients underwent laparotomy; in 41 cases, the sigmoid was gangrenous and associated with more complications (X2 = 15.68; p < 0.001). Non-operative treatment (NOT) like endoscopic, fluoroscopic or rectal tube decompression was performed in 135 patients and successful in 79% with a 38-57% recurrence rate. A total of 73 patients subjected to elective surgery: 50 underwent sigmoid resection; 17 had surgery for HD. Clinicians should consider SV in all children with abdominal pain, distension and vomiting. Gangrene carries a higher morbidity. After successful NOT we recommend counselling about the recurrence risk and definitive surgery should be advised. HD is frequent in newborns but sometimes found in older children.